Pengaruh Rasio Profitabilitas, Rasio Likuiditas, Pertumbuhan Perusahaan Terhadap Opini Audit Going Concern - Kimberli Kimberli; Budi Kurniawan (Jurnal Akuntansi, 2021)
Abstract The problems that will be discussed in this journal are regarding the relationship between Profitability Ratios, Liquidity Ratios and Company Growth on Audit Delay. The research method used in this study uses secondary data. The population in this study is all Real Estate companies and the Property sub-sector registered on the BEI which are listed on the Indonesia Stock Exchange in 2017, 2018, 2019 and 2020. The sampling method in this study is purposive sampling. The criteria for companies that are sampled are companies that publish audited financial statements for four consecutive years and use the rupiah currency, so that the total number of samples in this study is 165 data. The independent variables in this study are Profitability Ratios, Liquidity Ratios and Company Growth. The dependent variable in this study is audit delay. The data analysis technique used is the Logistics Regression Test with the use of Software Eviews 10. The results of the analysis show that profitability has no significant effect on going concern audit opinion. Meanwhile, company growth and liquidity have no effect on going concern audit opinion. Keywords: Going Concern Opinion, Profitability, Liquidity, and Company Growth